Effects of Compensation, Training and Development, and Supervisor Support Toward Organizational Commitment of Multigeneration Employees in a Public Sector Organization in Indonesia - Nurul Hanifah; Muhammad Irfan Syaebani (Indonesia Banking School, 2016)
This research aims to examine effect of compensation, training and development, and supervisor support toward organizational commitment of Generation X and Y workforce in State Comptroller Agency (BPKP - Badan Pengawas Keuangan dan Pembangunan). Sample for this research is 110 Gen X workers and 52 Gen Y workers in deputies’ office of Central BPKP in Jakarta. This research indicates that training and development has positive influence on organizational commitment on both Gen X and Gen Y workers. However, research finding is unable to show the difference effect of compensation, training and development, and supervisor support toward organizational commitment between Gen X and Gen Y workers. Thus, the effect of independent variables toward dependent variables is indifferent for both generations and the implication of this research is discussed.